Do Poor Functional Outcomes and Higher Morbidity Following Emergency Repair of Giant Hiatus Hernia Warrant Elective Surgery in Asymptomatic Patients? - Bujoreanu, Iulia; Abrar, Daniya; Lampridis, Savvas; Date, Ravindra (Frontiers in Surgery, 2021)
Background: Patients with a giant hiatus hernia may present with acute symptoms caused by obstruction, strangulation, perforation and uncontrolled bleeding. Emergency surgical repair has been associated with significant mortality and even greater morbidity. The aim of this study is to investigate the short-term outcomes following emergency repair of giant hiatus hernias. Methods: Data were retrospectively collected for all patients who underwent emergency surgical repair of giant hiatus hernia in a university teaching hospital between 2009 and 2019. Outcomes were short-term morbidity and mortality. We also assessed the association of clinical predictor covariates, including age, ASA class and time to surgery, with risk for major morbidity. Results: Thirty-seven patients with a median age of 68 years were identified. Following surgery, 9 patients (24.3%) developed organ dysfunction that required admission to the intensive care unit. Two patients (5.4%) underwent revision surgery and 3 (8.1%) developed pneumothorax that necessitated chest drain insertion. The commonest complication was pneumonia, which occurred in 13 patients (35.1%). Two deaths (5.4%) occurred within 30 days from surgery. Conclusions: Emergency repair of giant hiatus hernia is associated with high rates of major morbidity, which includes interventions, repeat surgery and admission to the intensive care unit. Larger studies are warranted to investigate how major morbidity may be predicted by preoperative variables.